Identification of early-induced broadly neutralizing activities against transmitted founder HIV strains. (1st January 2023) - Lucas, Julie; Lin, Li-Yun; Paul, Nicodème; Laumond, Géraldine; Klingler, Jéromine; Schmidt, Sylvie; Frappier, Julia; Essat, Asma; Meyer, Laurence; Gordon, Alicia Castro; Goujard, C.é.cile; Bahram, Seiamak; et al.
Abstract : Objectives: Broadly neutralizing antibodies have been proposed as key actors for HIV vaccine development. However, they display features of highly matured antibodies, hampering their induction by vaccination. As protective broadly neutralizing antibodies should be induced rapidly after vaccination and should neutralize the early-transmitted founder (T/F) viruses, we searched whether such antibodies may be induced following HIV infection. Design: Sera were collected during acute infection (Day 0) and at viral set point (Month 6/12) and the neutralizing activity against T/F strains was investigated. Neutralizing activity in sera collected from chronic progressor was analyzed in parallel. Methods: We compared neutralizing activity against T/F strains with neutralizing activity against non-T/F strains using the conventional TZM-bL neutralizing assay. Results: We found neutralizing antibodies (nAbs) preferentially directed against T/F viruses in sera collected shortly after infection. This humoral response evolved by shifting to nAbs directed against non-T/F strains. Conclusion: Although features associated with nAbs directed against T/F viruses need further investigations, these early-induced nAbs may display lesser maturation characteristics; therefore, this might increase their interest for future vaccine designs.